Lipid Oxidation Products and the Risk of Cardiovascular Diseases : Role of Lipoprotein Transport - Ahotupa, Markku (MPDI, 2025)
Cholesterol has for decades ruled the history of atherosclerotic cardiovascular diseases (CVDs), and the present view of the etiology of the disease is based on the transport of cholesterol by plasma lipoproteins. The new knowledge of the lipoprotein-specific transport of lipid oxidation products (LOPs) has introduced another direction to the research of CVD, revealing strong associations between lipoprotein transport functions, atherogenic LOP, and CVD. The aim of this review is to present the evidence of the lipoprotein-specific transport of LOP and to evaluate the potential consequences of the proposed role of the LOP transport as a risk factor. The associations of cholesterol and lipoprotein LOP with the known risk factors of CVD are mostly parallel, and because of the common transport and cellular intake mechanisms it is difficult to ascertain the independent effects of either cholesterol or LOP. While cholesterol is known to have important physiological functions, LOPs are merely regarded as metabolic residues and able to initiate and boost atherogenic processes. It is therefore likely that with the increased knowledge of the lipoprotein-specific transport of LOP, the role of cholesterol as a risk factor of CVD will be challenged.